(untitled) (World Bulletin of Public Health, 2022)
This is a painful swelling of the appendix of the cecum; a finger-like sac that connects to the large intestine, on the right side lower abdomen complications and, in most cases, peritonitis can be treated by prompt removal of the appendix and cleaning inside the abdomen to prevent inflammation. Without prompt treatment, peritonitis can cause death. Appendicitis occurs when swollen lymph nodes in the appendix wall due to gastrointestinal infections or any mean in the body or blockage of the lumen of the appendix due to bacteria that interact within it, causing it to enlarge and its inflammation. The data collected was studied at Ramadi teaching hospital from 600 patients, of whom 400 underwent a conventional appendectomy, and 200 patients were treated with laparoscopy and it was called by this name, the removal of this existing appendix Near the area where the small intestine and the large intestine connects in the human body, which ranges from 5 meters in length To 11 cm does not cause complications and harm to the body, which means that it has no role ,The appendix can be removed using two different techniques Laparoscopic surgery It is the most common technique in which a surgeon performs three or four incisions Small incisions (incisions) in the abdomen and the appendix is removed from a small camera known as an endoscope Using special surgical tools , The surgeon then sutures the large intestine, which was the appendix Adhesive tapes are attached to them and seal the cracks with steri-strips and The second technique is open surgery (a few the surgeon cuts the right abdomen, and cuts a small lower abdomen the appendix removes the appendix through it and then bandages the wound with strips-steri